2019
DOI: 10.3390/genes10100764
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Categorization of Loeys-Dietz Syndrome Based on 24 Novel Families and Literature Data

Abstract: Loeys-Dietz syndrome (LDS) is a connective tissue disorder first described in 2005 featuring aortic/arterial aneurysms, dissections, and tortuosity associated with craniofacial, osteoarticular, musculoskeletal, and cutaneous manifestations. Heterozygous mutations in 6 genes (TGFBR1/2, TGFB2/3, SMAD2/3), encoding components of the TGF-β pathway, cause LDS. Such genetic heterogeneity mirrors broad phenotypic variability with significant differences, especially in terms of the age of onset, penetrance, and severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…Our data also identify the OFT (orthologous to the mammalian aortic root) as the main compartment affected in alk5a mutants. Interestingly, many of the phenotypes we observed are similar to defects associated with aortopathies in clinical settings, pathologies often derived from mutations in TGF-β pathway genes (Loeys et al, 2006;Matyas et al, 2006;Camerota et al, 2019). At the morphological level, we observed that alk5a mutants present a thinning of the OFT outer wall, similar to patients affected by aortic aneurysms prone to dissection (Van Puyvelde et al, 2016;Jana et al, 2019).…”
Section: Clinical Perspective Of the Alk5a Cardiac Phenotypesupporting
confidence: 66%
See 1 more Smart Citation
“…Our data also identify the OFT (orthologous to the mammalian aortic root) as the main compartment affected in alk5a mutants. Interestingly, many of the phenotypes we observed are similar to defects associated with aortopathies in clinical settings, pathologies often derived from mutations in TGF-β pathway genes (Loeys et al, 2006;Matyas et al, 2006;Camerota et al, 2019). At the morphological level, we observed that alk5a mutants present a thinning of the OFT outer wall, similar to patients affected by aortic aneurysms prone to dissection (Van Puyvelde et al, 2016;Jana et al, 2019).…”
Section: Clinical Perspective Of the Alk5a Cardiac Phenotypesupporting
confidence: 66%
“…Here, we established, optimized, and combined functional analyses of the adult zebrafish heart using echocardiography and MRI with a morphological characterization of the cardiac compartments and adjacent vessels using µ-CT. As a proof-of-concept, we examined alk5a/tgfbr1 mutants as TGFBR1 genetic variants in humans have been associated with aortic aneurysms and diseases of the great vessels, the diagnosis of which is most often recognized in young adults (Loeys et al, 2005;Loeys et al, 2006;Matyas et al, 2006;Weerakkody et al, 2018;Camerota et al, 2019). We show that the use of this multimodal preclinical imaging strategy allows for a robust dissection of adult zebrafish cardiac phenotypes, even in the presence of high variability between samples of the same genotype.…”
Section: Introductionmentioning
confidence: 99%
“…This case highpoints that while molecular diagnosis in patients with a full-blown phenotype is mainly confirmatory, in those with an incomplete presentation it turns out to be fundamental, since these individuals might not be diagnosed or even be misdiagnosed. Indeed, considering the clinical overlap not only between the different EDS subtypes but also with other HCTDs [1,9,28,30,32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], differential diagnosis is not always forthright. Differential diagnosis includes the molecularly unsolved hEDS that shares with cEDS gJHM and more than a few (muco) cutaneous signs; however, hEDS patients usually show a lower degree of scarring and skin hyperextensibility and much more striking gJHM complications [1,7,28,29,50].…”
Section: Discussionmentioning
confidence: 99%
“…In one subject without mutation of the FBN1 gene, a pathogenetic variant of the TGFBR2 gene (a gene involved in transforming the growth factor β (TGF-β) signaling pathway) was present; this led to a diagnosis of LDS, a genetic condition overlapping MSF in an aortic root aneurysm and risk of dissection, in skeletal features and habitus [ 23 ]. The suggested follow-up in LDS syndrome is the same as for MFS.…”
Section: Resultsmentioning
confidence: 99%
“…In eight patients (8.9%), two genetic variants were identified: A pathogenetic variant in FBN1 and another variant of uncertain significance in the COL1A2, COL5A1, or COL5A2 genes. These genes, when functionally altered, cause Ehlers–Danlos syndrome—the classic type and, on the basis of a recent study [ 23 ], could act as modifiers of phenotypes. The presence of diverticula was found in eight out of the 62 (12.9%) patients with a single mutation and in one out of eight (12.5%) patients with a double mutation ( p > 0.99).…”
Section: Resultsmentioning
confidence: 99%